Sodium Cyclamate Effect on Nondisjunction Frequency of Drosophila melanogaster Meigen - Putri, Eka Pratama; Fauzi, Ahmad (Proceedings of the International Conference on Green Technology; Vol 8 No 1 (2017): Proceedings of the International Conference on Green TechnologyDO - 10.18860/icgt.v8i1.530, 2017)
Sodium cyclamate is one of the artificial sweeteners that have potential health concerns. In this research, a study was conducted to examine the effects of sodium cyclamate administration on nondisjunction frequency of Drosophila melanogaster. ♂ the homozygous ebony body was crossbred with ♀ homozygous wild-type fly and was fed with food containing 0% (control group), 5%, 10%, and 15% sodium cyclamate. Based on ANOVA result, F count was 29.578 with the p-value 0.000 < 0.05. Thus, the null hypothesis was rejected and research hypothesis states there were significant differences of nondisjunction frequency was accepted. Flies treated with sodium cyclamate had significantly higher nondisjunction than the control flies. Administration of 15% sodium cyclamate caused nondisjunction with the greatest frequency.